Role of Brand Trust in Mediating Influence of E-Wom and Product Quality on Purchasing Decisions - Putu Kelvin Indrawan; I Putu Gde Sukaatmadja; Ni Nyoman Kerti Yasa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Mumubrandedbag operates in the fashion industry. This research investigates how brand trust mediates the impact of electronic word of mouth (eWOM) and product quality on purchase decisions in Denpasar City. The study included 100 consumers chosen through purposive sampling. Data collection was conducted through surveys using questionnaires with a 5-point Likert scale and analyzed using Smart PLS. The findings showed that while eWOM has a positive yet negligible effect on purchasing decisions, it significantly impacts brand trust. Product quality has a significant impact on both brand trust and purchasing decisions. However, brand trust does not have a significant effect on purchasing decisions and does not mediate the influence of eWOM and product quality on purchasing decisions. These findings offer valuable insights for marketing management and suggest future research could include additional variables like brand image, store atmosphere, and price suitability, and expand the research scope